Mutual interference between memory encoding and motor skills: the influence of motor expertise - Monz, Annalena; Morbe, Kathrin; Klein, Markus; Schaefer, Sabine (Frontiers in Psychology, 2023)
In cognitive–motor dual-task situations, the extent of performance decrements is influenced by the attentional requirements of each task. Well-learned motor skills should be automatized, leading to less interference. This study presents two studies combining an episodic memory encoding task with well-practiced motor tasks in athletes. Study 1 asked 40 rowers (early teenagers to middle adulthood) to row on ergometers at slow or fast speeds. In study 2, Taekwondo athletes (n = 37) of different skill levels performed a well-practiced sequence of martial arts movements. Performing the motor task during encoding led to pronounced performance reductions in memory in both studies, with costs of up to 80%. Cognitive costs were even larger when rowing with the fast compared to the slow speed in study 1. Both studies also revealed decrements in motor performances under dual-task conditions: Rowing became slower and more irregular (study 1), and the quality of the Taekwondo performance was reduced. Although higher-level athletes outperformed others in motor skills under single-task conditions, proportional dual-task costs were similar across skill levels for most domains. This indicates that even well-practiced motor tasks require cognitive resources.